Historicist interpretation of the Olivet Discourse and the sixth seal 2. Corrective, reinterpretation, and saving the historical Jesus - Charlesworth, Scott D. (2017)
The reference in the sixth seal to signs in the heavens that accompany the parousia (Rev 6:12-17) corrects the flawed interpretation of Daniel found in Mark 13 par. Because the heavenly signs occur in the sixth of seven seals, the consecutive openings imply a sequencing of events and, therefore, a delayed parousia. Similarly, the greatest tribulation of all time did not occur in connection with the fall of Jerusalem as Matthew has it (24:21). John is shown a 'great multitude' of people coming out of a 'great tribulation' subsequent to his day (Rev 7:14). This great tribulation, with its primary point of reference in the 'time, times, and half a time' of Daniel (7:25; 12:7-10; 11:32-35) and its counterparts in Revelation (13:1-8; cf. 11:2-3; 12:6, 14), is to be followed by an even greater tribulation involving the whole earth (13:11-17). Further, since the first plague falls on those with the mark of the beast (16:2), the seven last plagues are associated with this second, unprecedented tribulation. As for the timing of the parousia, the parallels between the sixth seal and the seventh plague imply that the second coming is to accompany the opening of the sixth seal and outpouring of the seventh bowl (16:17-20). Thus, the Apocalypse corrects the Olivet Discourse in an implicit admission that the historical Jesus had misunderstood Daniel. In doing so it reinterprets Daniel and provides a foundation for historicist interpretation of that apocalyptic book and, possibly, of the Apocalypse itself.
Keywords: Apocalypse; Historicism; Olivet Discourse; corrective; Historical Jesus; reinterpretation; sixth seal